Autonomic cardiac activity among novice archers during baseline, shooting, and recovery - Tok, S.; Dal, N.; Zekioglu, A.; Çatikkas, F.; Balikçi, I.; Dogan, E. (The Journal of Strength and Conditioning Research, 2020)
In the present study, we aimed to investigate whether heart rate variability (HRV) of novice archers may vary during baseline, shooting, and recovery periods. In addition, we aimed to explore whether HRV may have different patterns between successful and less successful archers and man and woman archers. The sample consisted of 39 (12 woman) novice archers ranging in age from 21 to 27. Baseline HRV activity was measured in the first stage of the experiment. Then, participants shot 10 arrows, from 18 m to an 80 cm diameter target, whereas their HRV was measured. Lastly, HRV recovery response was measured immediately after shooting. HRV was represented as low frequency (LF), high frequency (HF), and LF/HF ratio. When considering the entire sample, repeated measures of analysis of variance (ANOVA) indicated that only HF power differed among baseline, shooting, and recovery periods [F(2, 76) = 6.90, p = 0.002, Omega2 = 0.15]. When the data partitioned, based on the median split of the shooting scores, repeated measures of ANOVA demonstrated that none of the HRV components differed in the less successful group from baseline to recovery. However, in the successful group, both LF [F(1.47, 30.98) = 4.75, p = 0.024, Omega2 = 0.18] and HF [F(1.54, 32.37) = 6.61, p = 0.007, Omega2 = 0.24] power significantly differed among baseline, shooting, and recovery. No differences were found between man and woman archers in terms of HRV indices. The results of the present study indicated that physical activities requiring the use of perceptual motor skills, in addition to physical qualities, may lead to different HRV responses. Moreover, coaches aiming to develop archers' shooting accuracy may take into account LF power measured during an arrow shooting session.